2013
DOI: 10.7314/apjcp.2013.14.11.6703
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the XRCC3 Thr241Met Polymorphism and Cervical Cancer Risk: a Meta-analysis

Abstract: In subgroup analysis, significant associations were found for Asians under all genetic models. Conclusions: Our meta-analysis suggested the XRCC3 Thr241Met polymorphism might not act as a cervical cancer risk factor overall. However, in subgroup analysis, a significant association was found in Asians under all genetic models. The association should be studied with a larger, stratified population, especially for Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Based on a similar hypothesis of influencing radiotoxicity, the association of XRCC3 polymorphisms with cancer risk has also been extensively evaluated. Evidence from meta-analysis supports a positive association between the XRCC3 p.Thr241Met polymorphism and the risk of bladder cancer [ 56 57 ], breast cancer [ 58 59 ], cervical cancer [ 60 61 ] and hepatocellular carcinoma [ 62 63 ]. However, in glioma [ 64 65 ], NSCLC [ 66 67 ], colorectal cancer [ 68 69 ] and gastric cancer [ 70 71 ] patients, the associations were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a similar hypothesis of influencing radiotoxicity, the association of XRCC3 polymorphisms with cancer risk has also been extensively evaluated. Evidence from meta-analysis supports a positive association between the XRCC3 p.Thr241Met polymorphism and the risk of bladder cancer [ 56 57 ], breast cancer [ 58 59 ], cervical cancer [ 60 61 ] and hepatocellular carcinoma [ 62 63 ]. However, in glioma [ 64 65 ], NSCLC [ 66 67 ], colorectal cancer [ 68 69 ] and gastric cancer [ 70 71 ] patients, the associations were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Ling-Yan Qin et al showed that the XRCC3 Thr241Met polymorphism might not act as a cervical cancer risk factor. However, in subgroup analysis, a significant association was found in Asians under all genetic models (Qin et al, 2013). The association should be studied with a larger, stratified population.…”
mentioning
confidence: 87%
“…XRCC3 sequence variations may affect the function of the encoded protein and consequently alter its DNA repair capacity (Matullo et al, 2001). Moreover, recent meta-analyses have suggested that the T241M polymorphism is associated with an increased risk of lung and cervical cancers (Qiu et al, 2013;Qin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%